Sustentabilidade nos negócios: reflexões e desafios - Ikarugi, Vitor da Silva (Universidade Federal de São Carlos, 2023)
New technologies are being increasingly used in the business world, but not always in a sustainable way. There are different movements in the business world that raise questions about how it is possible to build a management (private or public) that produces technology and is still sustainable. Within the idea of innovation in management, there are paths such as technological innovation, organizational innovation and even behavioural organization. In addition to this concept, sustainability is also part of the main objective, as each innovation work structure currently must undergo a sustainable restructuring. Therefore, the objective of this article is to understand how sustainable innovations can exist in a business environment, that is, how to carry out an economically sustainable path in a company. The path to understanding the objective, which will make use of bibliographical research as a research methodology, will be traced through the understanding of what sustainability and innovation in management mean. It is concluded, therefore, that sustainability in the business environment is possible, but requires a continuous dialogue between companies and the world around them, always prioritizing man and the environment in which he is inserted.
Sustainability in businessses: reflections and challenges
Keywords: Sustentabilidade; Inovação; Empresas; Sustainability; Innovation; Companies; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS